DAMPAK MEDIA APLIKASI ZOOM SEBAGAI MEDIA PEMBELAJARAN ONLINE SELAMA PANDEMI COVID-19 - Jahrir, Andi Sahtiani; Tahir, Muhammad (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2020)
The Impact of the Zoom Application on Online Learning during the Covid-19 Pandemic. The purpose of this study was to determine the impact of the Zoom application in online learning during the Covid-19 pandemic. The essence of the problem is what are the processes, constraints, and variations in the form of applying the Zoom application to online learning during the Covid-19 pandemic? In this study using a qualitative research type. The population in this study were students of the State University of Makassar, while the sample selection was students of the Indonesian Language and Literature Department who conducted lectures by applying the zoom application in their lectures provided by the lecturer. The results of the analysis found that the Zoom application is the application that many lecturers choose to interact directly, the variation of online learning used in the zoom application is to combine various other learning applications, namely Kelase, Google Classroom, Google Form, What Up, and others. The constraints faced are the large amount of data or quotas in use, even the material described is not finished because the effective time provided by Zoom is only 40 minutes, also with unsupportive signals, so that sometimes exiting the application, and the difficulty of collecting tasks.